Myopic reactions to performance feedback: Different decision makers, different decisions - GREVE, Henrich R. (Institutional Knowledge at Singapore Management University, 2016)
The behavioral theory of the firm predicts that problemistic search and organizational change occurs after comparing performance with the aspiration level, and this prediction has been strongly supported. The bounded rationality assumption in the behavioral theory of the firm suggests that such search is often myopic. However, we still lack theory explaining the source of myopia and how myopia influences decision makers choosing search directions when performance feedback indicates a problem. In this study, we address the relationship between myopia and search direction. We develop theory on how decision maker cognitions and knowledge formed by their past experiences underlie coalitions that direct myopic search, leading to connections between the decision making group composition and the likelihood of choosing different actions when making organizational changes. We apply the theory to a well-known reaction to performance feedback—mergers and acquisitions—and show that the experience of the decision maker and the composition of the key decision making group—board of directors—interacts with performance feedback to affect the choice of action—the type of acquisition target—as an outcome of myopic search.